MERITOCRACY AND BRAZILIAN SOCIETY - Lívia Barbosa (RAE: Revista de Administração de Empresas, 2014)
Thought on elements that underlie the demand for meritocracy at public and private organizations in Brazil and the discourses structured around their implementation.